2012
DOI: 10.3897/zookeys.179.2601
|View full text |Cite
|
Sign up to set email alerts
|

New Coleoptera records from New Brunswick, Canada: Cerambycidae

Abstract: Five species of Cerambycidae, Acmaeops discoideus (Haldeman), Anelaphus villosus (Fabricius), Phymatodes species (CNC sp. n. #1), Sarosesthes fulminans (Fabricius), and Urgleptus signatus (LeConte) are newly recorded for New Brunswick, Canada. All but Acmaeops villosus are new to the Maritime provinces. Phymatodes testaceus (Linnaeus) is removed from the faunal list of the province as a result of mislabeled specimens, records of Phymatodes maculicollis LeConte are presented confirming the presence of this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, our trapping results also suggest that Anticosti Island might be a hot spot for N. upiformis in eastern North America. We caught 333 specimens on this large island, which is far more than any other report from other regions of Quebec (7 specimens from 5 locations; this study), Newfoundland (4 specimens; Smith and Hurley 2005), New Brunswick (17 specimens; 5 in Webster et al 2012; 4 as indicated by Webster pers. comm.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…However, our trapping results also suggest that Anticosti Island might be a hot spot for N. upiformis in eastern North America. We caught 333 specimens on this large island, which is far more than any other report from other regions of Quebec (7 specimens from 5 locations; this study), Newfoundland (4 specimens; Smith and Hurley 2005), New Brunswick (17 specimens; 5 in Webster et al 2012; 4 as indicated by Webster pers. comm.…”
Section: Discussionmentioning
confidence: 68%
“…Strangely, most specimens (8 out of 12 for which collection dates were available) found in collections were collected after 15 July while nearly all specimens collected on Anticosti Island were collected before that date, even if it is a much cooler area. Moreover, all specimens reported from Newfoundland (Smith and Hurley 2005), New Brunswick (Webster et al 2012; Webster pers. comm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations